Breast Cancer Prevention Behavior among Women of Reproductive Age: Knowledge, Attitude, and Family Support - Triharini, Mira; Armini, Ni Ketut Alit; Rahmi, Zulfia (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer is the leading cause of cancer deaths among women. Many breast cancer patients come to health services at an advanced stage. Most women of reproductive age in some countries have not done breast cancer prevention due to various factors. This study aims to identify the correlation of knowledge, attitude, and family support with breast cancer prevention behavior. A cross-sectional approach was carried out on 110 women of reproductive age in the Pacar Keling Community Health Center, Surabaya, selected by cluster sampling. The inclusion criteria were women 15 – 49 years who live together with their family. The exclusion criteria were women diagnosed with breast tumors or breast cancer. The independent variables were knowledge, attitude, and family support. The dependent variable was breast cancer prevention behavior. Data were collected using questionnaires. The data analysis was using statistic test Spearman’s rho (α ≤ 0.05). There was a correlation between knowledge (p = 0.002, r = 0.290), attitude (p = 0.004, r = 0.271), and family support (p = 0.001, r = 0.326) with breast cancer prevention behavior. Prevention of breast cancer in women of reproductive age can be done optimally if they have good knowledge and positive attitude. Family support is a reinforcing factor so that prevention of breast cancer in women of reproductive age can be done consistently